Acaricidal Efficacy of Diatomaceous Earths on Different Life Stages of Acarus siro L. and Tyrophagus putrescentiae (Schrank) - Maria C. Boukouvala; Constantin S. Filintas; Nickolas G. Kavallieratos (Insects)
Acarus siro L. and Tyrophagus putrescentiae (Schrank) (Sarcoptiformes: Acaridae) are cosmopolitan mite species in food storage and processing environments, infesting a wide variety of commodities. In the current study, the diatomaceous earths (DEs) InsectoSec and Fossil Shield were evaluated for wheat protection against adults, larvae, and nymphs of A. siro and T. putrescentiae. Both DEs were examined at 200 and 500 ppm at 1, 2, and 5 days post-exposure. The efficacy of both formulations against A. siro and T. putrescentiae life stages depended on dose and exposure. Mortality of A. siro reached 100% in larvae, 99.3% in nymphs, and 95.6% in adults by day 5 at 500 ppm of InsectoSec. Similarly, Fossil Shield achieved almost complete larval mortality (99.3%) of A. siro at 500 ppm. For T. putrescentiae, 100% mortality was observed for larvae at both doses of InsectoSec and for adults or nymphs at 500 ppm by the fifth day. Fossil Shield caused a similar mortality to larvae, reaching 97.0% and 100%, at 200 and 500 ppm, respectively, after 5 days. Our findings indicate that InsectoSec and Fossil Shield can be used as sustainable management tools against A. siro and T. putrescentiae.